2010
DOI: 10.1088/0953-8984/22/50/505501
|View full text |Cite
|
Sign up to set email alerts
|

Pseudopotential and full-electron DFT calculations of thermodynamic properties of electrons in metals and semiempirical equations of state

Abstract: In the present work, we compare the thermal contribution of electrons to thermodynamic functions of metals in different models at high densities and electron temperatures. One of the theoretical approaches, the full-potential linear-muffin-tin-orbital method, treats all electrons in the framework of density functional theory (DFT). The other approach, VASP, uses projector-augmented-wave pseudopotentials for the core electrons and considers the valent electrons also in the context of DFT. We analyze the limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Satisfaction of some computational threshold for the smallest non-negligible occupation number requires an increasingly large set of those virtuals to be considered with increasing T. Concurrently there is [36] found that for ambient density Al, the PAW pressure deviated from the all-electron value at about T = 5-6 eV. This is less than 10% of the magnitude of the LSDA 2p atomic KS eigenvalue (about 70 eV).…”
Section: Finite Temperatures a Pseudopotentials And Level Populamentioning
confidence: 99%
See 2 more Smart Citations
“…Satisfaction of some computational threshold for the smallest non-negligible occupation number requires an increasingly large set of those virtuals to be considered with increasing T. Concurrently there is [36] found that for ambient density Al, the PAW pressure deviated from the all-electron value at about T = 5-6 eV. This is less than 10% of the magnitude of the LSDA 2p atomic KS eigenvalue (about 70 eV).…”
Section: Finite Temperatures a Pseudopotentials And Level Populamentioning
confidence: 99%
“…That threshold is directly related to basis set size or, equivalently, the plane-wave cutoff. We know of only one study of any of these questions [36]. In it, all-electron calculations with the full-potential linearized muffin-tin orbital methodology were used to benchmark projector augmented wave (PAW) calculations with a plane wave basis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shell effects in condensed matter caused by both pressure and temperature were investigated by DFT [31]. In this case the thermal excitation of inner electrons takes place which causes oscillations of some thermodynamic functions.…”
Section: Resultsmentioning
confidence: 99%
“…At T > 0 the quantum molecular dynamics (QMD) method allows us to simulate a cubic supercell with up to 1000 ions; in the Born-Oppenheimer approximation quantum electrons are treated by DFT while the movement of classical ions obeys Newton's second law. As some electrons in a pseudopotential DFT approach are included into an invariable core this method is restricted both on temperature and density because of the excitation of core electrons [31]. Also in QMD additional error may appear when some particles move very close to each other at high enough temperatures [32].…”
Section: Methods Of Calculationmentioning
confidence: 99%